Surfaces Roughness And Microstructure Studies On Eggshell Surfacesbanana Inner Trunk Skin Texture - Tan, Jack Hoe (Universiti Sains Malaysia, 2017)
Eggs and bananas were consumed by human being in their daily life, which indicates that a lot of eggshells were being thrown and banana plants were cut down as waste. Eggshell (Chicken, Ch; Duck, D; and Quail, Q) was often wrongly believed being unsuitable to be one of engineering materials due to its brittleness and the fiber extracted from banana inner trunk (B) was also wrongly perceived as not strong enough because of its soft and wet properties. The aims of this reaserch were to describe the surface roughness by using surface profilometer and microstructure studies on each diversity of eggshell surfaces and inner banana trunk according their maturity stages (Growth, G, Maturation, M and Senescence, S) towards skin texture by using Scanning Electron Microscope (SEM) and to discover the further engineering applications of the eggshell and inner banana trunk. Distribution and thickness of organic cell membrane attached to the eggshell determined the surface roughness of the inner surface of the eggshell (Ch: Ra=1.247μm, Rq=1.606μm; D: Ra=1.171μm, Rq=1.449μm; Q: Ra=1.237μm, Rq=1.561μm) and grains size determined the surface roughness of the outer surface of eggshell (Ch: Ra=1.327μm, Rq=1.645μm; D: Ra=1.170μm, Rq=1.585μm; Q: Ra=1.627μm, Rq=2.057μm). Cellulosic properties were the factors affecting the surface roughness of the banana inner trunk in lateral (Inner Surface: {BG: Ra=1.237μm, Rq=1.568μm; BM: Ra=1.807μm, Rq=2.249μm; BS: Ra=11.203μm, Rq=14.973μm}; Outer Surface: {BG: Ra=0.832μm, Rq=1.020μm; BM: Ra=1.267μm, Rq=1.553μm; BS: Ra=17.166μm, Rq=20.837μm}) and longitudinal directions (Inner Surface: {BG: Ra=1.140μm, Rq=1.418μm; BM: Ra=1.354μm, Rq=1.668μm; BS: Ra=3.593μm, Rq=4.411μm}; Outer Surface: {BG: Ra=0.515μm, Rq=0.654μm; BM: Ra=0.862μm, Rq=1.090μm; BS: Ra=1.531μm, Rq=1.942μm}). New invention of these materials will able to create a zero waste environment by recycling these materials for useful applications.